George Orwell: The English Dissident as Tory Anarchist. (11th May 2012) - Wilkin, Peter
Abstract : This article examines the nature of George Orwell's Tory anarchism, a term that he used to describe himself until his experiences in Spain in 1936. The argument developed here says that the qualities that Orwell felt made him a Tory anarchist remained with him throughout his life, even after his commitment to democratic socialism. In fact, many of those qualities (fear of an all‐powerful state, respect for privacy, support for common sense and decency, patriotism) connect the two aspects of his character. The article explains what the idea of a Tory anarchist means, describing it as a practice rather than a coherent political ideology, and moves on to examine the relationship between Eric Blair, the Tory anarchist, and George Orwell, the democratic socialist. It makes the case for his Tory anarchism by drawing out recurring themes in his work that connect him to other Tory anarchist figures such as his contemporary Evelyn Waugh. Thus Tory anarchism is presented as a conservative moral critique of the modern world that can connect figures who hold quite radically different political beliefs.